De la mobilité des paysans tharu et de leurs chefs - Gisèle Krauskopff (Ateliers d'Anthropologie)
In 1978, Sagant devoted a pioneering article to "the magnitude and historical depth of Nepali migrations" which highlights the oppression of the new Nepalese administration and the role that British colonization of India played in intensifying migrations in early 19th century. The relevance of Sagant’s analysis is illustrated by a mass migration of Tharu peasants in 1805, from lands under the administrative supervision of a small Himalayan kingdom, towards land under British control. In this paper, I deal with the mobility of Tharu peasants living in the Terai region, which underwent a radical change at that time with the interference of the British and the establishment of an international border between two new nation states. My contribution takes a more general approach to the role of peasant mobility in social formations and to the contradictions generated by the establishment of state-controlled territories. These historical data shed light on Tharu social organization—the importance of common residences, large houses and house groups (villages), based on the necessarily collective farming of pioneer land—and Tharu farmers’ non-attachment to land, even the rejection of this attachment to avoid paying taxes and resist the control of the state. Sagant emphasised the decisive role played by local leaders in intensifying migration, with powers granted by the central administration that distorted traditional institutions. Tharu chiefs were no exception: a collection of archives (1726-1840) on a Tharu lineage shows the evolution of the status of one of these chiefs and the rupture caused by the control of the central administration and the emergence of nation states.